2013
DOI: 10.18553/jmcp.2013.19.5.408
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Clinical and Economic Effectiveness of Clinical Pharmacist Intervention in Secondary Prevention of Cardiovascular Disease

Abstract: BACKGROUND: Cardiovascular disease (CVD) is considered to be the main cause of death and one of the most common diseases affecting health care systems worldwide. Many methods have been used to improve CVD outcomes, one of which is to involve clinical pharmacists in the direct care of patients with CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
69
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 61 publications
1
69
0
2
Order By: Relevance
“…Indeed, research has demonstrated the effectiveness of pharmacistprovided disease management activities, including for hypertension. [4][5][6][7][8][9][10] Specific to hypertension, a recent systematic 94 Circulation July 14, 2015…”
Section: Editorial See P 75 Clinical Perspective On P 100mentioning
confidence: 99%
“…Indeed, research has demonstrated the effectiveness of pharmacistprovided disease management activities, including for hypertension. [4][5][6][7][8][9][10] Specific to hypertension, a recent systematic 94 Circulation July 14, 2015…”
Section: Editorial See P 75 Clinical Perspective On P 100mentioning
confidence: 99%
“…1 Results from the FAME trial 2 and other systematic reviews in hypertension 3 and cardiovascular disease 4 indicate pharmacist-led interventions are successful in increasing medication adherence and improving quality of care, especially among elderly patients with chronic diseases. Many of these interventions tend to be complex and may include a combination of medication reminders, frequent patient education or counseling, use of improved administration systems such as blister packs, and use of medication event monitoring systems.…”
mentioning
confidence: 99%
“…Many of these interventions tend to be complex and may include a combination of medication reminders, frequent patient education or counseling, use of improved administration systems such as blister packs, and use of medication event monitoring systems. [2][3][4] Apart from carrying out interventions directly targeted at improving medication adherence, pharmacists may also be required to conduct frequent comprehensive medication reviews for patients with multiple chronic illnesses to optimize therapy, decrease adverse events, and reduce pill burden, thereby improving medication adherence. 5 Yet, little information is available to accurately evaluate pharmacy store quality and thereby encourage quality improvement at the pharmacy store level.…”
mentioning
confidence: 99%
“…A systematic review from 2013 identified 59 studies, 45 of which were randomised, whose aim was to evaluate the clinical efficacy of pharmaceutical intervention in the secondary prevention of CVDs. The effectiveness of these interventions was considered high, reaching almost 70% [19]. Moreover, the interventions proposed by the pharmacists in the area of optimising pharmacotherapy achieve a high level of cardiologists' acceptability -during one of the tests 1416 (92%) of the 1541 pharmacists' clinical recommendations were accepted by the surgeons taking care of the patients [20].…”
Section: The Role Of the Pharmacist In The Treatment Of Cvdmentioning
confidence: 99%